The Influence of Career Development on Employee Performance in FIF Group Cikampek Karawang branch - Kania, Wulan; Kristanto, Yudi; Army, Widya Lelisa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Problems with inappropriate career development result in a problem phenomenon regarding a decrease in employee performance, where employees seem to be careless in their work, hasty in concluding a problem which results in work errors. The aim of this research is to determine the effect of career development on employee performance. This research using quantitative methods with associative techniques was carried out in FIF Group Cikampek Karawang branch with a population of 30 employees with data collection techniques using questionnaires. Based on the calculation results, a correlation coefficient of r = 0.854 and a determination coefficient of R = r was obtained.2 = 0.730. Testing the significance of the correlation obtained tcount (8,691) > t table (2.00) at α = 0.05, indicating that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between career development and employee performance can be accepted. This means that the higher the career development, the higher the employee performance will be. Meanwhile, the coefficient of determination of 0.730 indicates that 73% of the variation in Employee Performance. This research is motivated by the consequences that can be explained by variations in Career Development, the remaining 27% is determined by other factors outside of Career Development.